Correlation between Platelet Indices and PELOD-2 Score as Prognostic Markers in Pediatric Sepsis at Dr. Zainoel Abidin Hospital - Pratiwi, Sari Novita; Sovira, Nora; Edward, Eka Destianti; Herdata, Heru Noviat; Safri, Mulya; Ismy, Jufitriani (Media Publikasi Cendekia Indonesia, 2025)
To determine the correlation between Mean Platelet Volume (MPV) and Platelet Distribution Width (PDW) with Pediatric Logistic Organ Dysfunction (PELOD-2) scores as prognostic markers in pediatric sepsis. This prospective cohort study included 44 pediatric sepsis patients admitted to the PICU at Dr. Zainoel Abidin Hospital from July to September 2024. PELOD-2 scores and blood indices were assessed on admission (Day 1) and Day 3. Pearson correlation was used to analyze the relationship between variables. The majority of patients were female (59.1%) and under one year old (31.8%). By Day 3, 68.2% of patients exhibited MPV levels exceeding 10.4 fL. Significant moderate correlations were found between Day 3 MPV and PELOD-2 (r=0.410; p=0.006), Day 3 PDW and PELOD-2 (r=0.518; p=0.001), and the changes (Δ) in PDW versus PELOD-2 scores (r=0.471; p=0.005). Increases in MPV and PDW are significantly correlated with PELOD-2 scores, suggesting their potential utility as accessible prognostic markers in pediatric sepsis management.